Integrating toba batak culture in elementary school learning: an effort to strengthen the local identity of the nation's children - Mangido Nainggolan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This paper describes the implementation of Toba Batak culture-based learning in elementary schools and analyse the roles of teachers, schools, families, and traditional leaders in preserving local cultural values. The research background departs from the phenomenon of the weakening of the younger generation's attachment to Toba Batak culture due to globalisation and the dominance of digital popular culture. This study uses a qualitative method with a descriptive approach. Data were collected through participatory observation, in-depth interviews with teachers, principals, parents, and traditional leaders, and documentation of learning activities at Lumban Bulbul Elementary School in Toba. Data analysis was carried out through the stages of data reduction, data presentation, and thematic conclusion drawing. The research results indicate that Toba Batak culture-based learning in elementary schools is still in early stages and has not been fully integrated into the curriculum. Teachers have attempted to link local cultural elements through regional songs, folk tales, storytelling competitions, Tor Tor performances, and Ulos exhibitions. However, limited teaching materials, lack of training, and minimal collaboration with traditional institutions remain obstacles. Meanwhile, families remain the primary agents of cultural heritage transmission through the Batak language, participation in traditional ceremonies, and the instillation of the values ​​of Dalihan Natolu, Hamoraon, Hasangapon, and Hagabeon. Traditional leaders also play a role in maintaining cultural continuity through social activities and collaboration with schools. The research implications emphasise the need to develop local culture-based learning guidelines, teacher training on integrating cultural values ​​into the curriculum, and formal partnerships between schools and traditional institutions to ensure the sustainability of cultural preservation.